Determinants of neonatal mortality among neonates admitted to neonatal intensive care unit of Dessie comprehensive and specialized hospital, Northeast Ethiopia; An unmatched case-control study - Wake, Getu Engida; Chernet, Kalkidan; Aklilu, Almaz; Yenealem, Fentahun; Wogie Fitie, Girma; Amera Tizazu, Michael; Mittiku, Yohannes Moges; Sisay Chekole, Moges; Behulu, Geremew Kindie (Frontiers in Public Health, 2022)
Background: According to the world health organization, neonatal mortality is defined as the death of babies within the first 28 days of their lives. The newborn period is the most vulnerable period for a child's survival, with the bulk of neonatal deaths occurring in the first day and week? According to a recent study, about a third of all newborn deaths occur within the first day of life, and nearly three-quarters occur within the first week. This study aimed to assess the determinants of neonatal mortality among neonates admitted to the neonatal intensive care unit in Dessie comprehensive and specialized hospital, northeast Ethiopia. Methodology: Health institution-based unmatched case-control study was conducted among neonates admitted to Dessie comprehensive and specialized hospital, Ethiopia from February 1/2020 up to March 30/2020. After keeping cases and controls in separate frames, study participants were chosen using a simple random sampling procedure until the sample size was met. Epi data version 7.0 and SPSS version 25 were used for data entry and analysis respectively. P-value ≤ 0.05 was used as a cut point of statistical significance in multivariable binary logistic regression. Results: A total of 698 (233 cases and 465 controls) were participated in the study. Pregnancy induced hypertensions (AOR=3.02; 95% CI; 1.47-6.17), public hospital delivery (AOR=3.44; 95% CI; 1.84-6.42), prematurity (AOR=2.06; 95% CI; 1.43-2.96), being referred (AOR=4.71; 95% CI; 3.01-7.39) and hypothermia (AOR=2.44; 95% CI; 1.56-3.82) were determinant factors of neonatal mortality. Conclusion: Pregnancy-induced hypertension, public hospital delivery, prematurity, referral, and hypothermia were found to be the determinant factors of neonatal mortality. It would be important to give due attention to neonates delivered from mothers with a history of the hypertensive disorder. Besides better to give due attention to neonates delivered in public health institutions, prematurely delivered, referred, and hypothermic neonates. Lastly, further research should be conducted to investigate the additional determinants of neonatal mortality.